2015
DOI: 10.1111/maps.12396
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of trace element concentrations in the lunar magma ocean using mineral‐ and metal‐silicate melt partition coefficients

Abstract: This study uses experimentally determined plagioclase‐melt D values to estimate the trace element concentrations of Sr, Hf, Ga, W, Mo, Ru, Pd, Au, Ni, and Co in a crystallizing lunar magma ocean at the point of plagioclase flotation. Similarly, experimentally determined metal‐silicate partition experiments combined with a composition model for the Moon are used to constrain the concentrations of W, Mo, Ru, Pd, Au, Ni, and Co in the lunar magma ocean at the time of core formation. The metal‐silicate derived lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
16
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 104 publications
8
16
1
Order By: Relevance
“…Interpretation of our results can only utilize the last approach which is comparison of measured concentrations to previous studies where nuggets were thought to be avoided or minimized. Our melts typically have 2.5–20 ppm Ru, 87–300 ppm Pd, and 10–300 ppm Au, all of which are comparable to levels measured in previous studies across this temperature range (e.g., Righter et al 2015, 2018; Sharp et al 2015). There is one exception—in experiment #258, an HSE nugget clearly interfered with the analysis of garnet resulting in concentrations as high as 30–335 ppm of some HSEs in the analysis.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Interpretation of our results can only utilize the last approach which is comparison of measured concentrations to previous studies where nuggets were thought to be avoided or minimized. Our melts typically have 2.5–20 ppm Ru, 87–300 ppm Pd, and 10–300 ppm Au, all of which are comparable to levels measured in previous studies across this temperature range (e.g., Righter et al 2015, 2018; Sharp et al 2015). There is one exception—in experiment #258, an HSE nugget clearly interfered with the analysis of garnet resulting in concentrations as high as 30–335 ppm of some HSEs in the analysis.…”
Section: Resultssupporting
confidence: 87%
“…Testing magma ocean crystallization models for a multi‐element system including Os isotopes has been hindered by a dearth of partitioning data for the HSE, especially for phases such as deep mantle garnet, ringwoodite, and wadsleyite that may be present in the Martian mantle at conditions proposed by Debaille et al (2008). To build on our and others’ initial findings for HSE partitioning on low pressure (shallow melting) phases (Brenan et al 2003, 2005; Righter et al 2004; Sharp et al 2015; Malavergne et al 2016), we examine HSE partitioning at higher PT conditions and search for potential deep mantle host phases for Re, Pt, and Os. We begin to examine the partitioning behavior of HSEs between these deep mantle phases with a study of partitioning between majorite garnet (gt), olivine (oliv), wadsleyite (wads), and silicate liquid (melt).…”
Section: Introductionmentioning
confidence: 99%
“…); plagioclase/melt studies that include Au, Pd, and Ru (Sharp et al. ); and olivine/melt systems at somewhat oxidized conditions (Ru, Rh—Brenan et al. , ).…”
Section: Highly Siderophile Element Content Of Martian Mantle and Meltsmentioning
confidence: 99%
“…It is notable that the review of Righter et al (2000) indicated almost no data for chromite/melt pairs, as well as only preliminary HSE partition coefficients (some for FeO-free systems) for the major silicates-olivine, orthopyroxene, and clinopyroxene. There have been several pointed studies covering significant territory for the HSE including new data for chromite/melt pairs (Rh, Ru, Os, and Ir; Righter et al 2004;Brenan et al 2012); a systematic study of Re ; clinopyroxene/melt studies that included three HSEs (Rh and Ru-Hill et al 2000;Pt-Righter et al 2004); plagioclase/melt studies that include Au, Pd, and Ru (Sharp et al 2014); and olivine/melt systems at somewhat oxidized conditions (Ru, Rh-Brenan et al 2003. There are still many gaps in our knowledge such as for specific elements (Rh and Ir), or specific phases (orthopyroxene, plagioclase, garnet), but there are enough data to conduct a modeling exercise related to magmatism and mantle evolution for Mars.…”
Section: Silicates and Oxidesmentioning
confidence: 99%
“…In summary, although data remain limited, most of the evidence currently suggests a lunar mantle with strong depletions in HSE, and approximately chondritic relative abundances. Some recent studies have sought to constrain siderophile element abundances in the lunar magma ocean by determining distribution coefficients that are relevant to reverse modelling the abundances present in presumed products of magma ocean crystallisation, in particular anorthositic crust (e.g., Sharp et al, 2015). However, many questions remain and much further work will be required to advance this issue sufficiently.…”
Section: The Moonmentioning
confidence: 99%